A Population-Based Study Comparing Child (0-4) and Adult (55-74) Mortality, GDP-Expenditure-on- Health and Relative Poverty in the UK and Developed Countries 1989-2014. Some Challenging Outcomes - Colin Pritchard; Richard Williams; Tamas Hickish; Mark Wallace (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Purpose: To compare the UK Child (0-4) and Adult (55-74) Mortality with twenty developed countries 1989-2014 to explore whether the UK has lower priorities for children? Design: WHO data on Child and Adult mortality examined within context of World Bank GDPExpenditure- on-Health (%GDPEH) data and Income Inequality i.e Relative poverty. Settings: 21 developed countries. Patients: National populations. Outcome Measures: Child and Adult mortality rates per million (pm) population between 1989-2014. Confi dence Intervals compares UK with other developed countries (ODC); odds ratios of average European to UK mortality calculated. Correlations explore links between mortalities, %GDPEH and Income Inequality. Important Results: Highest average 1980-2014 %GDPEH is USA 12.6%, the lowest UK 7.0%. European average 8.5% a UK to European odds ratio 1:1.21. Widest Income Inequality was USA 15.9 times, UK 13.8 was third, European average 8.5times. Child Mortality fell in every country but eleven signifi cantly better than Britain. Highest was USA 1383pm the UK fourth at 967pm. European average 728pm yielded a  European to UK odds ratio of 1:1.33. Income Inequality and CRM signifi cantly correlated (RHO=+0.6188 p<0.001) and lowest Private: Public %GDP ratio and highest CMR (Rho=+0.3805 p<0.05). Adult Mortality fell substantially in every country but UK signifi cantly greater reductions than Seventeen counties. European average 9545pm to UK 10,754pm gave a European to UK odds ratio of 1:1.13. Conclusion: Implications; Britain's results suggest a higher priority is given to adult health than children. The socio-economic context in which UK Child health operates appears to disadvantage UK children, indicating the need to address income inequalities and at least match European average health funding.